Therapeutic immunization of highly active antiretroviral therapy-treated HIV-1-infected patients: safety and immunogenicity of an HIV-1 gag/poly-epitope DNA vaccine. - Dorrell, L; Yang, H; Iversen, A; Conlon, C; Suttill, A; Lancaster, M; Dong, T; Cebere, I; Edwards, A; Rowland-Jones, S; Hanke, T; Mcmichael, A (2005)
In view of the global emergency posed by lack of access to highly active antiretroviral therapy (HAART) and the limitations of current drug regimens, alternative therapeutic strategies are urgently needed. Cellular immune responses elicited by HIV-1 exert some control over virus replication, therefore the enhancement of HIV-1-specific responses by therapeutic vaccination might lead to viral containment without HAART. We evaluated the safety and immunogenicity, in HIV-1-infected individuals under HAART suppression, of a DNA vaccine, pTHr.HIVA.